Pretrial Detention in Russian Criminal Justice: Sociological Analysis of the Probability of Pretrial Detention and its Influence on Court Decisions - Titaev, Kirill (Journal of Economic Sociology, 2014)
This article is based on the sample of 10 000 decisions of Russian criminal courts and series of expert interviews with judges, investigators, prosecutors and attorneys. In the text, I analyze the probability of pretrial detention and the influence of this decision on the following court behavior. Empirical data is the simple random sample from the decisions published on the websites of Russian district courts (the main level in the system of Russian criminal justice) during 2011. There are two groups of questions in the world scholarly discussion. The first group is bound up with the role of various strongly extralegal (like a gender and a race) and semi-extralegal (like a socioeconomic status and an educational level) characteristics of the defendant in the decision about pretrial detention or release. The second group deals with the effects of pretrial detention on other court decisions (dismissing of the case, the type of punishment and the length of incarceration). These questions are resolved in this article using regression models. The probability of pretrial detention in Russia is statistically significantly higher for unemployed defendants and defendants with informal criminal records. The fact of pretrial detention is closely associated with the probability of case dismissal. The defendants who are detained before trial have less probability of case dismissal. In addition, pretrial detention increases the probability of incarceration as a form of punishment. The linear influence of the pretrial detention on the length of incarceration is not statistically significant.